Ceralasertib-Mediated ATR Inhibition Combined With Olaparib in Advanced Cancers Harboring DNA Damage Response and Repair Alterations (Olaparib Combinations). (2021) - Mahdi, Haider; Hafez, Navid; Doroshow, Deborah; Sohal, Davendra; Keedy, Vickie; Do, Khanh T.; LoRusso, Patricia; Jürgensmeier, Juliane; Avedissian, Manuel; Sklar, Jeffrey; Glover, Colin; Felicetti, Brunella; et al.
Abstract : PURPOSE: Poly (ADP-ribose) polymerase (PARP) inhibitors have emerged as promising therapy in cancers with homologous recombination repair deficiency. However, efficacy is limited by both intrinsic and acquired resistance. The Olaparib Combinations basket trial explored olaparib alone and in combination with other homologous recombination–directed targeted therapies. Here, we report the results of the arm in which olaparib was combined with the orally bioavailable ataxia telangiectasia and RAD3-related inhibitor ceralasertib in patients with relapsed or refractory cancers harboring DNA damage response and repair alterations, including patients with BRCA -mutated PARP inhibitor–resistant high-grade serous ovarian cancer (HGSOC). PATIENTS AND METHODS: Germline and somatic mutations had to be deleterious by COSMIC or ClinVar for eligibility. Olaparib was administered at 300 mg twice daily and ceralasertib at 160 mg daily on days 1-7 in 28-day cycles until progression or unacceptable toxicities. Primary end points were confirmed complete response (CR) or partial response (PR) rates and clinical benefit rate (CBR; CR + PR + stable disease [SD] at 16 weeks). RESULTS: Twenty-five patients were enrolled, with median four prior therapies. Five patients required dose reductions for myelosuppression. Overall response rate was 8.3% and CBR was 62.5% among the entire cohort. Two of five patients with tumor harboring ATM mutation achieved CR or SD ongoing at 24+ months, respectively (CBR 40%). Of seven patients with PARP inhibitor–resistant HGSOC, one achieved PR (–90%) and five had SD ranging 16-72 weeks (CBR 86%). CONCLUSION: Olaparib with ceralasertib demonstrated preliminary activity in ATM -mutated tumors and in PARP inhibitor–resistant BRCA1/2 –mutated HGSOC. These data warrant additional studies to further confirm activity in these settings.